2005
DOI: 10.1111/j.1468-2419.2005.00226.x
|View full text |Cite
|
Sign up to set email alerts
|

Does time management training work? An evaluation

Abstract: In an increasingly competitive business environment, organisations have sought to increase productivity and reduce costs. The consequences of this for many employees include increased workloads, longer working hours and greater time pressures which, the evidence suggests, are linked to stress, high rates of absence and turnover. At the same time there has been an increasing emphasis on the desirability of achieving work/life balance for individuals. In pursuit of these apparently conflicting demands it has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
1
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(77 citation statements)
references
References 46 publications
4
70
1
2
Order By: Relevance
“…but on the other side private primary school teachers do good planning in advance due to good administrative system and accent ability teacher. Trainings can bring positive change in the attitude and behaviour of teachers to maintain and manage their time skills, as the training programs on time management and outcomes with respect to the effectiveness of time management training were found effective and after their continuous evaluation it was also found that the participants were remained engage in time management behaviours more frequently after attending training program (Green & Skinner, 2005;King et al, 1986;Macan, 1994;Slaven & Totterdell, 1993;Van Eerde, 2003) and there is a positive relation between time management training and performance (Hall & Hursch, 1982;King et al, 1986;Orpen, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…but on the other side private primary school teachers do good planning in advance due to good administrative system and accent ability teacher. Trainings can bring positive change in the attitude and behaviour of teachers to maintain and manage their time skills, as the training programs on time management and outcomes with respect to the effectiveness of time management training were found effective and after their continuous evaluation it was also found that the participants were remained engage in time management behaviours more frequently after attending training program (Green & Skinner, 2005;King et al, 1986;Macan, 1994;Slaven & Totterdell, 1993;Van Eerde, 2003) and there is a positive relation between time management training and performance (Hall & Hursch, 1982;King et al, 1986;Orpen, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…TM helps professionals to improve their job efficiency by allocating time appropriately to each of their various job tasks (Hall & Hursch, 1982;Orpen, 1994;Schuler, 1979). This, in turn, helps improve workers' outcomes and enable them to work smarter in the private sector (Green & Skinner, 2005) for maximising the product. TMS-related job demands and expectations are increasing daily and affect whether a job is feasible or not (Institute for Educational Leadership, 2000, p. 12).…”
Section: Time Management and Performancementioning
confidence: 99%
“…Professionals who manage their time report less emotional exhaustion, which is the most important factor in professional burnout (Peeters & Rutte, 2005). Those who undergo TM training also report greater job satisfaction (Macan et al, 1990), motivation and work/home balance (Green & Skinner, 2005). Satisfaction and satisfaction-related factors have been shown to fundamentally contribute to employees' performance (Judge et al, 2001), even though every organisation faces limited resources, time and skills (Ajzen, 1991).…”
Section: Time Management and Performancementioning
confidence: 99%
“…Furthermore, the additional advantages of time management have been highlighted by secondary data authors as being more productive (Green andSkinner, 2005, Alexander andDobson, 2008), having more energy to accomplish tasks (Limoncelli, 2006, Becker andMustric, 2008) feeling less stressed (Bhugra andHowes, 2007, Brott, 2008), possibility to pursue personal interests, getting more things done (Green and Skinner, 2005) relating to others in more positive manner (Bhugra and Howes, 2007), and feeling better about self (Brott, 2008).…”
Section: Literature Reviewmentioning
confidence: 99%